Ferritin, morbid obesity and bariatric surgery - de Oliveira, Maria Rita Marques [UNESP]; Novais, Patrícia Fátima Sousa; Junior, Irineu Rasera; Detregiachi, Cláudia Rucco Penteado; Leandro-Merhi, Vânia Aparecida (My University, 2012)
The proposal for this chapter is, first, to discuss iron metabolism disorder as a risk factor for obesity-related diseases and what increased serum ferritin means in obese individuals. Later, the effect of surgery on dietary iron absorption, the high prevalence of anemia among operated patients and the impact of the procedure on serum ferritin will be discussed. Ferritin is a nonspecific marker of a great number of disorders. One of the main causes for the increase of serum ferritin is non-alcoholic fatty liver disease (NAFLD). NAFLD is manifested mainly in obese, type-2 diabetic and dyslipidemic individuals. Increased serum ferritin concentration is associated with increased blood pressure, hyperglycemia, hyperinsulinemia and hypercholesterolemia, representing a marker of poor prognosis in acute stroke and coronary artery disease. High ferritin is associated with the metabolic syndrome and reflects the inflammation process highlighted in fat tissue metabolism, atherosclerosis and diabetes. In this context, ferritin can be involved as a pro-oxidant factor. Increased ferritin can contribute to NAFLD pathogenesis and associated diseases, but the hypothesis that its increase is only a marker of the ongoing inflammatory process cannot be discarded. Retrospective data on the prevalence of anemia and behavior of ferritin before and after bariatric surgery in operated morbidly obese patients will also be presented. © 2012 by Nova Science Publishers, Inc. All rights reserved.